2022
DOI: 10.3892/ol.2022.13487
|View full text |Cite
|
Sign up to set email alerts
|

Six autoantibodies as potential differential biomarkers of hepatocellular carcinoma vs. liver cirrhosis and chronic hepatitis: A prospective multi‑institutional study

Abstract: Serum autoantibodies respond not only to tumor-associated antigens of hepatocellular carcinoma (HCC) but also to those of liver cirrhosis (LC) and chronic hepatitis (CH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The s-MK-positive group showed poor overall survival. An s-MK-positive rate was not associated with stage, and this tendency was similar to the pattern of serum autoantibodies, as previously reported (5,6). s-MK is induced not only by cancer but also by various factors such as inflammation and hemodynamics (21).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The s-MK-positive group showed poor overall survival. An s-MK-positive rate was not associated with stage, and this tendency was similar to the pattern of serum autoantibodies, as previously reported (5,6). s-MK is induced not only by cancer but also by various factors such as inflammation and hemodynamics (21).…”
Section: Discussionsupporting
confidence: 88%
“…However, its diagnostic performance is unsatisfactory, with low sensitivity and specificity. To improve the diagnosis of HCC, advances in biomarker detection techniques have led to the identification of several new biomarkers, such as autoantibodies and s-MK (4)(5)(6). s-MK, an emerging serum biomarker, activates several cell surface receptors to modulate various biological activities and is significantly increased in HCC (7).…”
Section: Introductionmentioning
confidence: 99%
“…One study with multiple TAAbs including anti-p16 in PC patents indicated that autoantibody to p16 showed the highest sensitivity (30.4%) in PC patients across 6 TAAbs ( P53, p16, p62, Survivin, IMP1) [16], in which, the performance of anti-p16 is similar to that in our current study. Anti-Sui1 is [23,9] the most frequently detected and evaluated autoantibody in HCC and Okada's study showed the highest sensitivity for the detection of HCC among six autoantibodies [21]. However, no report has been seen in PC, thus autoantibody to Sui1 is a newly discovered marker for the detection of PC.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, autoantibodies to nine proteins TAAs including Guanine Nucleotide-Binding Protein Subunit Alpha-11 (GNA11), Mesothelin (MSLN), Guanine Nucleotide Binding Protein, Alpha Stimulating (GNAS), CCAAT/Enhancer-Binding Protein Alpha (CEBPA), Murine Double Minute 2 (MDM2), Cyclin-Dependent Kinase Inhibitor 2A (CDKN2A or P16), eukaryotic translation initiation factor 1 ( eIF1 or Sui1), nucleobindin (Calnuc), Phosphatase and Tensin homolog (PTEN) which were previously studied in other types of cancer [17][18][19][20][21][22] were detected by Enzyme-Linked Immunosorbent Assay (ELISA) in serum samples from pancreatic cancer patients and normal controls, as well as serum samples collected before and after chemotherapy, with the following objectives: (1) whether the autoantibodies corresponding to the nine target proteins have positive reactions in PC patients;…”
mentioning
confidence: 99%